Endobronchial carcinoid presenting as Focal bronchiectasis in a young woman with systemic lupus erythematosus. Issue 10 (28th October 2021) - Nasir, Noreen; Akhlaq, Safia; Shehzad, Talha; Fatimi, Saulat
Abstract: Non‐resolving pulmonary symptoms in a patient with SLE require evaluation to exclude rare pulmonary lesions, such as carcinoid tumors. Abstract : This case affirms the fact that non‐resolving pulmonary symptoms in a patient with SLE require evaluation to exclude rare pulmonary lesions, such as carcinoid tumors.